2017
DOI: 10.1021/acs.molpharmaceut.7b00710
|View full text |Cite
|
Sign up to set email alerts
|

Rational Targeting of Cellular Cholesterol in Diffuse Large B-Cell Lymphoma (DLBCL) Enabled by Functional Lipoprotein Nanoparticles: A Therapeutic Strategy Dependent on Cell of Origin

Abstract: Cancer cells have altered metabolism and, in some cases, an increased demand for cholesterol. It is important to identify novel, rational treatments based on biology, and cellular cholesterol metabolism as a potential target for cancer is an innovative approach. Toward this end, we focused on diffuse large B-cell lymphoma (DLBCL) as a model because there is differential cholesterol biosynthesis driven by B-cell receptor (BCR) signaling in germinal center (GC) versus activated B-cell (ABC) DLBCL. To specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 46 publications
11
52
0
Order By: Relevance
“…combined HDL‐like nanoparticles with B‐cell receptor (BCR) signaling inhibitor ibrutinib, which respectively targeted cellular cholesterol uptake and BCR‐associated de novo cholesterol synthesis. They achieved cellular cholesterol reduction and induced apoptosis in resistant activated B‐cell (ABC) DLBCL cell lines . Pinheiro et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…combined HDL‐like nanoparticles with B‐cell receptor (BCR) signaling inhibitor ibrutinib, which respectively targeted cellular cholesterol uptake and BCR‐associated de novo cholesterol synthesis. They achieved cellular cholesterol reduction and induced apoptosis in resistant activated B‐cell (ABC) DLBCL cell lines . Pinheiro et al .…”
Section: Discussionmentioning
confidence: 99%
“…They achieved cellular cholesterol reduction and induced apoptosis in resistant activated B-cell (ABC) DLBCL cell lines. 46 Pinheiro et al used LDL or cholesterol-rich microemulsions (LDE) that bind to LDL receptors as carriers of antineoplastic agents to concentrate those drugs into cancer tissues. 47 Moreover, targeting cholesterol uptake disruption, Guillaumond et al revealed that shRNA silencing of LDLR, in pancreatic tumor cells, profoundly reduced uptake of cholesterol and altered its distribution, decreased tumor cell proliferation, and limited activation of extracellular regulated protein kinases 1/2 survival pathway.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…Ramos cell line) and DLBCL (e.g. SUDHL4 cell line), is accompanied by compensatory increases in the expression of genes required for de novo cholesterol synthesis (21). In fact, our data showed lymphoma cells not initially sensitive to HDL NP-mediated cholesterol depletion, including activated B cell (ABC) lymphoma (e.g.…”
Section: Introductionmentioning
confidence: 63%
“…Scavenger receptor type B-1 (SCARB1) is a high-affinity receptor for cholesterol-rich high-density lipoproteins (HDL), which has been implicated as a target in human cancers based upon its role in cancer cell cholesterol uptake (17)(18)(19)(20)(21)(22)(23)(24)(25) and in membrane-anchored second messenger signaling pathways (21,(26)(27)(28)(29), among other factors (30)(31)(32)(33). Our group developed cholesterol-poor high-density lipoprotein (HDL)-like nanoparticles (HDL NPs) to target and tightly bind SCARB1 to prevent the cellular uptake of cholesterol ester from HDLs (21,24,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation